solve for "x"

chanman3

New member
Joined
Dec 11, 2010
Messages
2
For some reason I just can't get past this problem.

1/a = 1/b + 1/x
lcd - abx

(abx)1/a = (abx)1/b + (abx)1/x

Then I get to bx = ax + ab

Where do I go from there?
 
chanman3 said:
For some reason I just can't get past this problem.

1/a = 1/b + 1/x
lcd - abx

(abx)1/a = (abx)1/b + (abx)1/x

Then I get to bx = ax + ab

Where do I go from there?

Since you are trying to solve for x, get all terms containing x on one side of the equation, and everything else on the other side.

If you subtract ax from both sides, you'll have this:

bx - ax = ax + ab - ax
bx - ax = ab

Now....remove a common factor of x from both terms on the left side, and see if that helps.
 
thank you very much. I guess I was looking at it so long I couldn't see it. Love this site!
 
Top